Cobrança pelo uso do solo: taxa e preço - Vieira, Maria Eugênia Doin (2012)
The present study deals with some of the relevant topics concerning the charged fee over soil use that is demanded by Municipalities in lieu of the public service that suppliers, specially the concessionaires, render mainly under the regime of Public Law. A periodic charge is requested due to equipment maintenance of the infrastructure in the public municipal spaces. Although the demand of such charge remains specific to every municipality, getting close to the charge of a rate or price according to the institutional rule, it is possible to identify similar legal traits that guide this charging, allowing its demand an abstract study, in view of constitutional guidelines and applicable legal dispositions, aiming at the evaluation concerning this charged amount characterized as rate and price. The investigation made in this study involves Tax and Administrative Law issues, which are deepened according to its relevance for the developed analysis, therefore, with no intention to exhaust both topics. In order to approach this theme, the first part is a brief analysis of the tax constitutional system, as well as the specificities on public service rendering performed through concessions. Based on those considerations, the main features on charging for soil use are discussed, comparing them with the criteria regulating the rates, as relevant tax specie, together with the main characteristics on prices. Finally, conclusions are presented regarding the charges made on soil use and its compatibility with our Judicial Regulations